Crane Cloud: a resilient multi-cloud service layer for resource constrained settings - Bainomugisha, Engineer; Mwotil, Alex (Makerere University, 2021)
Whereas the main cloud providers have set up cloud services on stable infrastructure, developers and users situated in low-resource settings access cloud services and platforms using low-end computing devices that often connect to the Internet via slow mobile connections. These settings require custom software abstraction layers that consider such bandwidth constraints and intermittent connections as a rule rather than the exception. In this paper, we identify key challenges for developing for and accessing cloud services in resource constrained settings, namely, (1) Frequent Internet partitions and bandwidth constraints, (2) Data jurisdiction restrictions, (3) Vendor lock-in, and (4) Poor quality of service. To address these challenges, we propose a set of design considerations and properties for a resilient multi-cloud service layer, that includes: (1) Containerisation and orchestration of applications, (2) Service scheduling and replication, (3) Portability and multi-cloud migration, (4) Resilience to network partitions and bandwidth constraints, (5) Automated service discovery and load balancing, (6) Localised image registry, and (7) Support for platform monitoring and management. We present a prototype validation case study, Crane Cloud, an open source multi-cloud service abstraction layer built on-top of Kubernetes that is designed with inherent support for resilience to network partitions, microservice orchestration (deployment, scaling and management of containerized applications)a localized image registry, support for migration of services between private and public clouds to avoid vendor lock-in issues and platform monitoring. We evaluate the performance and user experience of Crane Cloud by implementing and deploying a computational and bandwidth intensive machine learning system shows lower response time compared when hosted on other public clouds.
Keywords: Microservices; Kubernetes; Containers; Orchestration; Low-resource settings; Portable cloud apps; Cloud native platforms